Variation in the COI gene of the freshwater pearl mussel Margaritifera margaritifera from River Vuokkijoki - Välilä, Santtu; Knott, Emily; Ieshko, E. P.; Veselov, A. E.; Taskinen, Jouni (Pleiades Publishing; Russian Academy of Sciences, 2017)
The freshwater pearl mussel Margaritifera margaritifera L. is one of the most endangered freshwater mussels in the world. Effective conservation of threatened species requires not only ecological, but also genetic information from the target species and populations. Since low genetic diversity can reduce the ability of a species to adapt to environmental changes, maintaining genetic diversity has been identified as one of the key elements in successful conservation programs. We examined genetic variation of the freshwater pearl mussel from the River Vuokkijoki, Karelia, Russia. We sequenced a fragment of the cytochrome c oxidase subunit I gene (COI) from 22 individuals and compared the data to 32 previously published COI sequences available in GenBank. We identified 10 different COI haplotypes in the sequenced samples, three of which had not been previously reported. Our results show that the River Vuokkijoki has high genetic diversity and suggest that the colonization of this northern freshwater pearl mussel population might have occurred from multiple and even distant refugia. Therefore, the freshwater pearl mussel population of the River Vuokkijoki is valuable for the conservation of the whole species. peerReviewed